Bandgap tuning for transition metal oxides via PEGylation - Jha P.A.; Mishra J.N.; Yadav G.; Kumar Tanti H.; Ranjan A.K.; Jha P.K.; Singh P. (My University, 2025)
Bandgap engineering is controlled manipulation of the bandgap of materials/meta-materials to achieve desired properties. The electrical and optical properties of materials are significantly affected by bandgap tuning; therefore, bandgap engineering is a powerful technique for designing electronic and optoelectronic devices. Compositional engineering, strain engineering, and nanoscience and technology are the three major fields associated with bandgap engineering. Any unique combination of this engineering can provide novel strategies to produce novel band-structured devices. In this method article, we have demonstrated how solvation energy can alter the bandgap energy, a fact that is generally ignored due to misconceptions about quantum/size confinement. Here, we prepare nanostructured transition metal oxides (Co3O4, CuO, and ZnO) with polyethylene glycol (PEG), and the method is termed PEGylation. We investigate the influence of PEGylation on the structural, electrochemical, and electronic nature of these oxides. It is observed that the bandgap tunability (7.33%) is maximum for ZnO. Our study suggests that band alteration is significantly correlated with the change in lattice parameters; however, it is orientation dependent as the correlation coefficient reduces to 0.85 from 1 for the change in lattice parameter b along the y-axis compared to the other two lattice parameters. Similarly, band alteration is also known to have some correlation with the electrochemical potential, but is surprisingly almost independent of size confinement. © 2024 IOP Publishing Ltd. All rights, including for text and data mining, AI training, and similar technologies, are reserved.